10.3389/fpsyg.2012.00132 (CrossRef Listing of Deleted DOIs, 2000)
INTRODUCTION: Antibody-drug conjugates (ADCs) have established roles in selected lymphoma settings, but the maturity, subtype distribution, and platform diversity of the clinical pipeline remain unclear. We mapped interventional trials to evaluate development trends, evidence maturity, molecular architecture, combination strategies, inactive development, and safety reporting. METHODS: We searched Trialtrove for Phase I-IV interventional trials evaluating at least one ADC in lymphoma, with actual or anticipated start dates through December 31, 2025. Non-ADC studies, observational studies, trials without lymphoma populations, and records with unconfirmed eligibility were excluded. Two reviewers independently screened and classified eligible records, with external verification when available. Analyses were descriptive; treatment effects and patient-level adverse-event incidences were not pooled. RESULTS: Of 482 records, 410 trials were included. Phase II was the largest category (193, 47.1%); 253 trials (61.7%) were single-arm and 76 (18.5%) were randomized. Among 837 trial-subtype pairs, diffuse large B-cell lymphoma (213, 25.4%) and classical Hodgkin lymphoma (135, 16.1%) were the most frequent and contained most late-phase activity. CD30 (181 trials), CD79b (104), CD19 (47), and CD22 (29) were the leading assigned targets. Of 50 unique ADC programs, 35 (70.0%) had not progressed beyond Phase I or Phase I/II. Tubulin inhibitors and cleavable linkers predominated. Among 92 inactive trials, the leading reported categories were recruitment or feasibility problems (30), unspecified reasons (28), and sponsor strategy (15). In 177 safety-evaluable trials, grade ≥3 adverse events were reported in 109, neutropenia in 98, infection in 79, and peripheral neuropathy in 69. DISCUSSION: Lymphoma ADC development has expanded, but trial growth has outpaced platform diversification and the generation of confirmatory evidence. Mature development remains concentrated in DLBCL, cHL, and a limited number of target-payload-linker platforms, while randomized, survival-based, and biomarker-driven evidence remains limited. Future priorities include subtype-specific targeting, platform diversification, randomized comparative studies, standardized safety reporting, biomarker-guided patient selection, and rational sequencing with immune and cellular therapies. Trial status and trial-level safety-reporting frequencies should not be interpreted as measures of clinical success or patient-level adverse-event incidence.